Edukasi Mengenai Pentingnya Kesadaran Masyarakat Mengetahui Tentang DAGUSIBU Dapatkan Gunakan Simpan Dan Buang Obat Dengan Baik - Astuty, Meilinda Windy; Aprilia, Apni; Oktaviani, N. Ajeng Tria; Pertiwi, Sherlina Dinda Ayu; Fitriana, Ai Ersa; Wijayanti, Mukti (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
The outreach program on DAGUSIBU (Get, Use, Store, Dispose) aims to enhance the knowledge of the community, particularly students of SMK Persada Sukabumi, regarding the wise use of medications. Research indicates that many individuals engage in self-medication without adequate knowledge, which can lead to errors in drug usage. This activity includes presentations on how to obtain medications correctly, safe storage practices, and the disposal of unused drugs. Questionnaire results revealed that before the outreach, 93% of students were unaware of DAGUSIBU. After the outreach, it is expected that students will be more prudent in managing their health and understand the importance of consulting medical professionals before consuming medications. This program aims to reduce the risk of drug misuse and increase community awareness about safe and effective medication use.